Hubungan antara Efikasi Diri dengan Resiliensi Menghadapi Ujian pada Siswa Kelas XII SMAN 1 Trawas - Okha Devi Anggraini; Esa Nur Wahyuni; Laily Tiarani Soejanto (Universitas Kanjuruhan Malang, 2017)
UNBK is the toughest challenge to students of class XII. Some students are hesitant and anxious to face exams. This is what makes they need to develop resilience and self efficacy. The purpose of this research is to know the relationship between self efficacy and resilience facing the exams. This research uses quantitative approach from / to correlational descriptive design. The subjects are the overall class XII students amounting to 182 students, so this research is a population research. Data were collected using a Likert instrument that measures self-efficacy and resilience facing exams. Data analysis techniques used descriptive analysis, prerequisite test in the form of normality test, and correlation test. Based on the results of the research can be seen most of the class XII students in SMA Negeri 1 Trawas have the level of self efficacy and resilience facing exams on the medium. From Product Moment correlation test results obtained r calculate of 0.716 with a significance level of 0.000 which indicates that the self efficacy variables are positively correlated and significant with resilience facing exams variables.